Pengembangan Lembar Kerja Peserta Didik (LKPD) Materi Menyelesaikan Masalah Terkait Operasi Hitung Pecahan Berbasis Contextual Teaching and Learning (CTL) di Kelas V SD N 15 Ulu Gadut Kota Padang - Ndruru, Silvia Yunita; Zainil, Melva; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to develop student worksheets to solve problems related to fraction counting operations based on Contextual Teaching and Learning. This research is a development research with 26 research subjects and carried out in SD N 15 Ulu Gadut Kota Padang. This development research uses the stages of analysis, design, development, implementationand evaluation. The average number of overall validations is 3,48 in the valid category. The results of the practicality questionnaire of the teacher's response were 93,75% with a very practical category, while for the student questionnaire the response was 96,76% with a very practical category. Based on the results of the validation and practical results it was stated that the developed student worksheets was valid and very practical. Thus, it can be concluded that the material student worksheets resolves problems related to the operation of fraction counting based on Contextual Teaching and Learning in grade V has been declared valid and very practical in learning.Keywords: development, student worksheet, Contextual Teaching and Learning.